Is the impact of opening the borders heterogeneous? - Costanza Naguib (University of Bern, Department of Economics, 2023)
We analyze the impact of an inflow of foreign workers on the wage distribution of residents in a small open economy like Switzerland. We exploit the fact that Swiss mobility regions were differently affected by the intensity and the timing of the Agreement on the Free Movement of Persons, depending on their distance from the national border. We extend the results by Beerli, Ruffner, Siegenthaler and Peri (2021) by analyzing heterogeneity in treatment effect via causal forests. We find statistically significant evidence that the treatment effect of opening the borders has been heterogeneous across age, education, and type of activity groups.
Keywords: C14; J31; 330; wage distribution; Bilateral Agreements; causal forest; Conditional Average Treatment Effect